Blockchain and Internet of Things: A bibliometric study. (January 2020) - Kamran, Muhammad; Khan, Hikmat Ullah; Nisar, Wasif; Farooq, Muhammad; Rehman, Saeed-Ur
Abstract: Blockchain is a distributed, decentralized and immutable digital ledger which records transactions across a global network of computers where the information is highly secure. Since its merger with other domains has solved numerous relevant problems, it has potential to resolve the issues of privacy and security in the domain of Internet of Things (IoT). IoT is reshaping the world into smart cities, smart farming, smart grids, smart transport, smart home, and smart healthcare systems. Thus, application of Blockchain in the domain of IoT gives birth to a new domain of Blockchain in IoT (BIoT). This research presents a bibliometric analysis of articles in BIoT domain, covering papers published in top journals and conferences, and finds research trends. It also explores diverse research areas, the most influential publications, top publication venues, top funding agencies and future research direction. This research can be a good learning point for young researchers to find attractive relevant research insights within BIoT.